2021
DOI: 10.33541/jet.v7i1.2313
|View full text |Cite
|
Sign up to set email alerts
|

English Education Master Students' Self-Regulated Learning Strategies in Academic Writing

Abstract: English Education Master Students’ Self-Regulated Learning Strategies in Academic Writing Kristian Florensio Wijaya Sanata Dharma University, Yogyakarta kristianwijaya500@gmail.com     Abstract There is a propensity for language teachers to handicap graduate students as independent, competent and strategic academic writers. Therefore, it is easier to discover graduate students struggling intensely to produce and publish qualified academic writing products to targeted j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…In this respect, Geng and Razali (2022), and Karagul and Seker (2021) revealed automated feedback significantly enhanced students' self-regulated learning while developing cognitive, metacognitive, motivational, and social strategies through daily practices. Wijaya (2021) found that selfregulated strategies help EFL students become metacognitively and motivationally independent, competent, and strategic academic writers. Additionally, the current study findings pointed to the effect of automated feedback on writing performance.…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this respect, Geng and Razali (2022), and Karagul and Seker (2021) revealed automated feedback significantly enhanced students' self-regulated learning while developing cognitive, metacognitive, motivational, and social strategies through daily practices. Wijaya (2021) found that selfregulated strategies help EFL students become metacognitively and motivationally independent, competent, and strategic academic writers. Additionally, the current study findings pointed to the effect of automated feedback on writing performance.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…The findings emphasized the significance of improving metacognitive regulatory skills for the writing performance of university EFL learners. Considerable research (Chen et Wijaya, 2021) investigated cognitive and metacognitive self-regulated learning in second language (L2) writing, highlighting its correlations with strategic interventions. The studies found that the most successful selfregulators are characterized by elevated cognitive, metacognitive, and motivational components of self-regulated learning.…”
Section: B Cognitive and Metacognitive Self-regulated Writing Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Husin and Nurbayani (2017) prompted Indonesian EFL teachers to continually instill more interactive academic writing activities to preserve their volition to rehearse their academic writing skills meaningfully. Wijaya (2021) discovered that the majority of graduate university EFL learners having been well-equipped with self-regulated learning skills were better in coping with all academic writing learning hurdles resulted in more satisfying academic writing achievements.…”
Section: Introductionmentioning
confidence: 99%